Prunus avium vegetal parts as a potential source of health benefits - Jesus, Fábio Miguel da Costa (2017)
The benefit effects of edible and medicinal plants are recognized since ancient times, being intimately linked with the capacity of them to synthesize a great variety of bioactive compounds, that can be used in their biological functions, for example in their defense against predators, but also as a supplement and/or medicinal drug due to their higher antioxidant power and anti-inflammatory capacity. Medicinal plant is defined as the entire plant, or parts, as for example leaves, fruits, roots, flowers, among others. In P. avium L. specie, the fruit, has been the target of several studies and its consumption has been encouraged. In addition to be largely appreciated due to its color, sweet taste, high contents of water and low-calorie value, sweet cherries also present a notorious antioxidant capacity. Relatively to leaves, flowers and stems of cherry tree, all of them are used as fertilizers. The flowers and stems are used as infusions, especially stems whose diuretic and sedative functions are well-known. Then and with the objective to extending the knowledge and applicability of stems, there were prepared two extracts, one hydroethanolic (50:50 v/v) and an infusion of the three matrices, and the phenolic profile and biological activity of the extracts were analyzed. LC-DAD analysis allowed the identification of thirty-one phenolic compounds: one hydroxybenzoic acid, thirteen hydroxycinnamic acids, three flavanols, three isoflavones, three flavanones and eight flavan-3-ols. Being sakuratenin derivative, 5-O-caffeolquinic acid and hydroxycinnamic derivative 1, the major compound in stems, leaves and flowers extracts, respectively. The antioxidant potential was evaluated by in vitro assays against DPPH, superoxide and nitric oxide radicals. All extracts revealed great potential in a dose-dependent manner for all assays. The hydroethanolic extracts of stems and leaves showed to be to the most active against DPPH radical (IC50 = 22.37 ± 0.29 µg/mL and IC50 = 27.29 ± 0.77 µg/mL, respectively). The same extracts obtained the best results to scavenging superoxide radicals IC50 = 9.11 ± 0.16 µg/mL and IC50 = 13.87 ± 0.41 µg/mL, for the hydroethanolic leaves and stems extracts, respectively. On the other hand, the infusion stems and hydroethanolic flowers extracts showed the highest antioxidant activity against nitric oxide radical (IC50 = 99.99 ± 1.89 µg/mL and IC50 = 123.38 ± 1.57 µg/mL), respectively. The antidiabetic activity was tested using the a-glucosidase enzyme, being the extracts of stems the most active, with an IC50 = 3.18 ± 0.23 µg/mL for infusion, and IC50 = 7.67 ± 0.23 µg/mL for hydroethanolic extract. Finally, the protective capacity of the human erythrocytes against oxidative damage of leaves, stems and flowers extracts was evaluated through the assays concerning the hemoglobin oxidation, lipid peroxidation and hemolysis. The hydroethanolic extract of stems was the most active against lipid peroxidation and hemolysis with IC50 = 26.20 ± 0.38 µg/mL and IC50=1.58 ± 0.18 µg/mL, respectively. On the other hand, the hydroethanolic extract of flowers showed the greater activity against the hemoglobin oxidation assay (IC50=12.85 ± 0.61 µg/mL). Considering the results obtained in this work, we can consider that leaves, stems and flowers of sweet cherry are a promising source of bioactive compounds, with antioxidant properties, protecting cells from the oxidative damage caused by free radicals, possess antidiabetic potential and protect the human erythrocytes. However, it is necessary to carry out new studies to demystify the use of these products as a possibility of natural formulations used as food supplements, nutraceuticals and pharmaceutical applications.